Confucianism and Autocracy : Professional Elites in the Founding of the Ming Dynasty - Dardess, John W. (University of California Press, 2023)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1983.